LINGKUNGAN MADRASAH DAN DAMPAKNYA TERHADAP PEMBENTUKAN KARAKTER DISIPLIN PESERTA DIDIK: STUDI FENOMENOLOGI DI MI SIROJUTTHOLIBIN KUANTAN SINGINGI - Mustofa Mustofa (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2021)
The formation of student discipline is influenced by many things, one of which is related to environmental conditions. Along with these views the study is designed to reveal how the madrassa environment shapes the discipline of learners. This research was conducted with a qualitative approach of phenomenological types, namely revealing the meaning contained in phenomena in madrasah environments. The results of the study are the environment mi Sirojuttholibin designed with conditions that can help the enforcement of student discipline, such as environmental refresh that prevents learners from leaving the madrasah environment during school hours, the availability of pamphlets that can be read by learners not to violate the rules. Madrasah has rules that direct learners to have a disciplined character. The atmosphere of the madrasah environment designed and the existence of madrasah policies related to discipline have an impact in shaping the character of the discipline of learners.